2007
DOI: 10.1007/s10288-007-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Capacitated lot-sizing with extensions: a review

Abstract: The capacitated lot-sizing problem (CLSP) is a standard formulation for big bucket lot-sizing problems with a discrete period segmentation and deterministic demands. We present a literature review on problems that incorporate one of the following extensions in the CLSP: back-orders, setup carry-over, sequencing, and parallel machines. We illustrate model formulations for each of the extensions and also mention the inclusion of setup times, multi-level product structures and overtime in a study. For practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 66 publications
0
53
0
2
Order By: Relevance
“…A variation of the CLSP is the discrete lot sizing and scheduling problem (DLSSP), where the planning horizon is divided into small periods which permit only the production of a single product. Quadt and Kuhn (2008) and Jans and Degraeve (2008) provided reviews of extensions of the basic CLSP, which included parallel machines, backorders, and setup times, among others. The capacitated single item lot sizing problem was finally reviewed in Brahimi et al (2006).…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A variation of the CLSP is the discrete lot sizing and scheduling problem (DLSSP), where the planning horizon is divided into small periods which permit only the production of a single product. Quadt and Kuhn (2008) and Jans and Degraeve (2008) provided reviews of extensions of the basic CLSP, which included parallel machines, backorders, and setup times, among others. The capacitated single item lot sizing problem was finally reviewed in Brahimi et al (2006).…”
Section: Content Analysismentioning
confidence: 99%
“…The major difference between the BSP and the JRP is that minor setups are not considered in the BSP, and that the BSP considers individual items, instead of production lots. Reviews of works that consider scheduling-issues in the CLSP can be found in Quadt and Kuhn (2008) and Jans and Degreave (2008). The sequence in which products are produced becomes important in this model if setup times and/or costs are sequence-dependent.…”
Section: Extended Models Models That Consider Scheduling Issuesmentioning
confidence: 99%
“…[18]- [20] and [5] the details of which is provided in this sub-section. We choose uniform distribution to generate parameters as this is traditionally used in the literature indicated above.…”
Section: Creating Test Instancesmentioning
confidence: 99%
“…Karimi et al [4] concluded that although lot sizing had been one of the favorite research areas in last few decades but still the realistic and practical variants of the CLSP, specially which considers backorders, setup times and setup carry-overs, had not received much attention. Also Quadt & Kuhn [5] gave an extensive review of the literature on the different extensions of the capacitated lot sizing problem. It is again evident from the review work of Quadt & Kuhn [5] that models with inclusion of backorders have received least attention in the past.…”
Section: Introduction and Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation